Influence of communication, collaboration, and decision-making skills on the efficacy of nurses in conducting neonatal resuscitation - Ika Rizki Anggraini; Kuswantoro Rusca Putra; Setyoadi Setyoadi (International Journal of Public Health Science (IJPHS), 2021)
This study aimed to analyze the influence of communication skill, collaboration, and decision-making upon self-efficacy upon Indonesia nurse’s self-efficacy in performing neonatal resuscitation. The research employed analytical descriptive design with cross-sectional study approach. The data were collected using questionnaire. Moreover, the research was carried out in Malang City area with the total of 75 nurses employed at neonatal intensive care unit (NICU) room and perinatology unit. Meanwhile, for data analysis, product moment correlation and linear regression were employed. The presence of influence of communication skill, collaboration, and decision-making upon nurse’s self-efficacy in performing neonatal resuscitation can be an inestimable reference for the need of objective evaluation on nurse’s capability and reflection on skills they have acquired. Communication skills p=0.000 (<0.05), collaboration p=0.000 (<0.05), preparation of results p=0.000 (<0.05) with the effectiveness of nurses in the management of neonatal resuscitation. In addition, multiple linear regression showed communication skills p=0.000, B=0.253 was the most dominant factor influencing nurses' self- efficacy when handling neonatal resuscitation in hospitals in Malang City of Indonesia. This study found an association related to communication skill, collaboration, and nurse decision making. Communication skills are the dominant factor influencing the efficacy of nurses in performing neonatal resuscitation care.